Tribological and thermal characterization of electron beam physical vapor deposited single layer thin film for TBC application. (24th June 2021) - Velusamy, Raja; Sakthinathan, G; Vignesh, R; Kumarasamy, A; Sathishkumar, Dhanalakshmi; Nithya Priya, K; Krishna, CS Vamsi
Abstract: Thin-film coatings have been commonly used in the automotive industry for a variety of applications. Thermal barrier coatings (TBCs) are designed to extend the life of combustors and turbine blades while mitigating high-temperature issues. In this study, an attempt has been made to develop a single-layer thin film as TBCs for engine applications. Yttria Stabilized Zirconia(YSZ) and Lanthanum Zirconate(LZ) were selected as the coating materials. The physical and chemical characteristics of target materials were studied using Scanning Electron Microscope (SEM), Energy Dispersive x-ray Spectroscopy (EDS), and x-ray Diffraction Analysis (XRD). FCD 400 has been taken as the substrates for this study. In general, TBCs thicknesses are usually about 100–300 μ m, while in this work, a coating thickness of 750 nm is attempted using EB-PVD and its performance was evaluated. The mechanical, tribological, and thermal behaviors of the uncoated and coated substrates were characterized as per ASTM standards. Maximum hardness of 3.68 GPa was observed on the YSZ coated substrates. The average Coefficient of Friction (COF) and Coefficient of Thermal Expansion(CTE) values of YSZ coated substrates were 0.334 and 1.33 × 10 –5 K −1, respectively, which were comparatively lower than LZ and uncoated substrates. On the contrary, the adhesive characteristics of YSZ and LZ coated substrates were enhanced, which was evident from their results of 6.28N and 6.19N respectively. The thermal conductivity of LZ coated substrates was found to be 3.2% lower than YSZ and 11% lower than uncoated substrates, respectively. From the results, it is observed that LZ thin film coating have better thermal properties than YSZ, which is best suited for TBCs application. Following evaluation of thin-film coatings, confirms that thin-film TBCs are a reliable approach for thermal and wear production as compared to thick TBCs, and their extended life could improve productivity and economic benefits for automotive industries.